Pengaruh Kualitas Pelayanan Aplikasi M-Paspor terhadap Kepuasan Pengguna Jasa Keimigrasian pada Kantor Imigrasi Kelas II Non TPI Agam - Deliano Akabar, Ghifa; Frinaldi, Aldri (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research is included in the category of quantitative research because this study seeks to test hypotheses by utilizing samples taken from the community. This research was conducted at the Immigration Office Class II Non TPI Agam. In this study, the sampling method used is the area sampling method because the work area has a wide scope. A total of 182 participants in this study were sampled. At the Class II Immigration Office of Non TPI Agam, the results showed that the variable quality of e-government services had a positive or significant effect on the service user satisfaction variable. This is by taking into account the significance value of 0.000 <0.05 for the variable quality of e-government services on the service user satisfaction scale. In the Class II Immigration Office of Non TPI Agam, the magnitude of the influence of the variable quality of e-government services on the service user satisfaction variable is 0.292 or equivalent to 29.2 percent. The amount of 29.2 percent is calculated using the Adjusted R value.